Precision livestock farming in buffalo species: a sustainable approach for the future - Gianluca Neglia; Roberta Matera; Alessio Cotticelli; Angela Salzano; Roberta Cimmino; Giuseppe Campanile (Revista Científica)
The growth of the world population that will occur in the next 30 years will be responsible for an increase in animal-derived food and proteins of animal origin. The livestock sector will be obliged to face new challenges, such as the reduction of environmental impact, the improvement of animal-derived food quality and safety, the reduction of antibiotics, and the increase in efficiency. One of the strategies that could be adopted is Precision Livestock Farming (PLF), recognized as the most sustainable tool to improve farm sustainability. It can be defined as “the continuous, automated, and real-time monitoring of production, reproduction, health, and welfare through the application of advanced information and communication technologies (ICT)”. In this new farm concept, animals, environment, machinery, and processes become “information objects” to enhance data; farm management and animals are defined as CITD systems: they are Complex, Individually different, Time- variant, and Dynamic. Several PLF technologies have been recently applied to buffalo species, improving some critical points of the farm, such as milking, nutrition, reproduction, and management. This short review reports some experiences carried out in buffalo species.